The Effect of Budget Planning and Budget Evaluation on Organizational Performance - Ramadhan, Muhammad Irfan; Rosmawati, Wati (Journal of Research in Construction, Communication, and Commercial, 2022)
This study aims to examine the effect of budget planning and budget evaluation on organizational performance in the Ministry of Agriculture, especially the Directorate General of Livestock and Animal Health. The variables used in this study are the independent variable (budget planning and budget evaluation) and the dependent variable (organizational performance). The method used by the author in this study is a quantitative method with a comparative causal approach. Data collection techniques were carried out using primary data obtained directly from the object of research and distributing questionnaires. The population in this study were all employees of the Directorate General of PKH, Ministry of Agriculture with a total of 90 respondents. The sample used was purpose sampling , namely the selection of a group of subjects based on certain characteristics or traits. The results of the study with multiple linear regression analysis based on the t test showed that budget planning had a positive and significant effect on organizational performance, budget evaluation had a positive and significant effect on organizational performance.